2014
DOI: 10.1260/1757-482x.6.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Moments-Based Formulation for the Transport and Deposition of Small Inertia Aerosols

Abstract: This paper introduces and evaluates a formulation for the modeling of transport and wall deposition of aerosols, written in terms of moments of the particle size distribution (PSD). This formulation allows coupling the moment methods with computational fluid dynamics (CFD) to track the space and time evolution of the PSD of an aerosol undergoing transport, deposition and coagulation. It consists in applying the quadrature method of moments (QMOM) to the diffusion-inertia model of Zaichik et al. [6], associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Such modeling can be used to track the particle size distribution of a nano-sized aerosol from its emission to the whole indoor environment, with immediate applications in the field of exposure modeling and computer aided design of protective equipments or ventilation strategies. As this model has also been validated for micro-sized aerosols undergoing transport, deposition and sedimentation in a recent paper (Guichard et al, 2014a), the use of this modeling approach extends to various indoor situations where aerosol size ranges from a few nanometers to a few micrometers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such modeling can be used to track the particle size distribution of a nano-sized aerosol from its emission to the whole indoor environment, with immediate applications in the field of exposure modeling and computer aided design of protective equipments or ventilation strategies. As this model has also been validated for micro-sized aerosols undergoing transport, deposition and sedimentation in a recent paper (Guichard et al, 2014a), the use of this modeling approach extends to various indoor situations where aerosol size ranges from a few nanometers to a few micrometers.…”
Section: Resultsmentioning
confidence: 99%
“…The size of this cell is specified as its center follows the constraint 30 y   , where y  is the dimensionless wall distance, according to the practical recommendation of Nerisson et al (2011). The implementation of the complete model into a commercial CFD solver is further detailed in Guichard et al (2014a). In the present paper, this model was implemented in the commercial code ANSYS Fluent 15.0.…”
Section: Boundary Condition For the Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the total number concentration reaches a peak soon after particle emission starts, and the number size distribution can be assumed as a bimodal shape. Guichard and Belut [13] combined the quadrature method of moments with a diffusion inertia model to simulate the dispersion of small and medium inertial aerosols in a ventilation chamber, and evaluated it in various test cases. Guichard and Belut [14] simulated numerically the nanoparticle distribution in a chamber ventilated by a turbulent flow at moderate Reynolds numbers, and showed that the highest reduction of particle number corresponds to the smallest and least compact nanoparticles.…”
Section: Introductionmentioning
confidence: 99%